Shielding the poor : social protection in the developing world - Lustig, Nora. (Washington, D.C. : Brookings Institution Press, 2001)
"The poor are most vulnerable to economic crises, natural disasters, or health shocks and are least able to cope with their economic consequences. Yet, for the most part, the poor have no access to social protection and insurance mechanisms. The lack of insurance and coping mechanisms may force the poor to reduce food consumption and investment in their children as well as deplete their scarce assets. These responses irreversibly and negatively affect the productive asset base of the poor and their earning capacity, possibly driving them into a vicious cycle of greater vulnerability and deeper poverty." "Shielding the Poor presents a group of studies on social protection in the developing world from leading researchers. These studies address the issue of vulnerability of the poor to adverse shocks and propose policies to increase their protection and coping capacity. The studies emphasize the need for building permanent institutional structures that help reduce and manage to risks that households face as part of a coherent long-term strategy to reduce poverty and promote social equity." "Policy interventions that improve social protection not only help shield the poor from the adverse consequences of shocks but also boost economic growth and reduce chronic poverty over the longer term by reducing the perverse effects of these shocks on the human and physical capital of the poor and on the economic activities that they undertake."--Jacket
Has aggregate income growth been effective in reducing poverty and inequality in Latin America? / Alain de Janvry and Elisabeth Sadoulet -- Social protection for the unemployed : programs in Latin America / Gustavo Márquez -- Heterogeneity and optimal unemployment insurance / Hugo A. Hopenhayn and Juan Pablo Nicolini -- Helping the poor manage risk better : the role of social funds / Steen Lau Jorgensen and Julie Van Domelen -- Insuring the economic costs of illness / Paul Gertler -- Coverage under old age security programs and protection for the uninsured : what are the issues? / Estelle James -- Social assistance on pensions and health care for the poor in Latin America and the Caribbean / Carmelo Mesa-Lago -- The safety net role of microfinance for income and consumption smoothing / Manfred Zeller -- Consumption smoothing and extended families : the role of government-sponsored insurance / Orazio Attanasio and José-Victor Ríos-Rull -- Social protection for the poor in the developed world / Timothy M. Smeeding and Katherin Ross Phillips.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Poor -- Developing countries; Public welfare -- Developing countries; Poverty -- Developing countries; Human services -- Developing countries; Structural adjustment (Economic policy) -- Social aspects -- Developing countries; POLITICAL SCIENCE -- Public Policy -- Social Policy; Human services; Poor; Poverty; Public welfare; Structural adjustment (Economic policy) -- Social aspects; Developing countries; Armoede; Sociale zekerheid; POBREZA -- PAISES EN DESARROLLO; BIENESTAR PUBLICO -- PAISES EN DESARROLLO; POBRES -- PAISES EN DESARROLLO